Hand‐foot‐and‐mouth disease in uruguay: Coxsackievirus A6 identified as causative of an outbreak in a rural childcare center. Issue 2 (20th September 2019) - Lizasoain, Andrés; Piegas, Sofia; Victoria, Matías; Da Silva, Edson E.; Colina, Rodney
Abstract: To know the epidemiological context of hand‐foot‐and‐mouth disease (HFMD) in a region of Uruguay and to identify the Enterovirus responsible for an outbreak in a rural childcare center in 2018. Swab samples from skin lesions and/or stools samples were collected from children suffering HFMD during an outbreak in a rural childcare center. Samples were subject to viral RNA extraction and reverse‐transcription polymerase chain reaction towards VP1 coding segment, to identify the Enterovirus type by sequencing and phylogenetic analysis. Total of 149 cases of HFMD affecting 98 boys and 51 girls were reported in Salto Province‐Uruguay in 2018. Total 60% of the cases were originated from outbreaks, which occurred in ten educative and childcare institutions from both urban and rural areas. Coxsackievirus‐6 (CV‐A6) was identified as responsible for one of the rural outbreaks. Uruguayan strains were more related to strains reported in Russia, Turkey, and Germany (2014‐2017) than to strains reported in Brazil and Argentina from 2015 to 2016. This is the first report of CV‐A6‐associated HFMD in Uruguay, evidencing a wide geographic range of the virus in the Latin American region. Our report also warns about CV‐A6‐associated HFMD during winter, contrarily to most reports that register HFMD during summer and fall seasons. Highlight: Hand‐foot‐and‐mouth‐disease in childcare institutions in Uruguay. Coxsackievirus‐A6 responsible for HFMD outbreaks. First report of CV‐A6 in Uruguay.